Entrepreneurial Value Creation: Study on Small Agri-tech Enterprise. (August 2022) - Swain, Sasmita; Patoju, Sri Krishna Sudheer; Manjushree, Paruchuru
In India, agriculture is labour intensive. The agricultural tasks such as sowing, weeding, spraying pesticides and harvesting are done manually. As it provides only seasonal employment, most rural labour force migrates to urban areas to earn a more sustainable income. This intrastate and interstate migration of the labour force creates a massive shortage in rural areas. This migration pushes the labour cost, leading to an increased price of agricultural produce. It is a significant concern for semi-medium and medium farmers with a limited budget for a small scale of operation. Non-availability of labourers pushed farmers to seek and adopt semi-mechanization in agricultural activities. The available farm machinery in the market is costly and primarily caters to the need of big farmers. Higher cost prevents semi-medium and medium farmers from using such machinery. They need farm machinery customized as per their need at an affordable price. Considering the problems faced by the horticultural farmers, 'Kakade Agro Equipment' designed farm machinery that could meet the requirements of the local farmers. The present case attempts to understand how small and medium enterprises operating at the local level are solving the problems of semi-medium and medium-scale horticultural farmers using technological innovation in a financially sustainable way.